Modellbasiertes Konzept zur vollautomatisierten Montageendprüfung von asynchron angetriebenen Getriebemotoren im lastlosen Zustand - Eichin, Dirk (Schriftenreihe des Instituts für Angewandte Informatik - Automatisierungstechnik, Karlsruher Institut für Technologie, 2014)
By the overall system of a fully automated final inspection of gearmotors, a new approach, in terms of the mass quality inspection of individually configured products according to the guidelines of a modular system, is presented. The challenge of the new approach is to map the product variety and to design effective visual and acoustic testing algorithms. Through a comprehensive consideration of the process the potential to increase the efficiency of the final inspection is demonstrated.